Do childbirth confidence, prenatal depression, childbirth knowledge, and spousal support influence childbirth fear in pregnant women? - Hyunjin Cho; Sukhee Ahn (Korean Society of Women Health Nursing, 2020)
Purpose This study investigated levels of childbirth fear and related prenatal factors (self-confidence for childbirth, prenatal depression, knowledge about childbirth, and spousal support) among pregnant women in South Korea. Methods A correlational study design was used to explore levels of childbirth fear and related prenatal factors in 200 pregnant women over 28 weeks of gestation. A self-administered questionnaire was used to measure fear of childbirth and related factors, such as self-confidence for childbirth, prenatal depression, knowledge about childbirth, and spousal support. Results One-third of the pregnant women were aged 35 years and older. Sixty-one percent of women were nulliparae, but only 26.0% had experienced prenatal education. The mean score for fear of childbirth was 66.99 out of 165. The prevalence of fear of childbirth was 72.0%, and childbirth fear was severe in 26.5% of the participants and moderate in 45.5%. Fear of childbirth was negatively related to self-confidence (r=-.45, p<.001), but positively related to prenatal depression (r=.21, p=.002). Two significant predictors were found to explain the fear of childbirth. Higher self-confidence for childbirth was associated with less severe fear of childbirth (β=-.44, p<.001), while higher prenatal depression was associated with more severe fear of childbirth (β=.13, p=.038). Conclusion The level of fear of childbirth was higher among pregnant women with lower self-confidence and higher prenatal depression. Reasonable evidence should be provided for implementing prenatal and childbirth classes to reduce pregnant women's depression and to increase their confidence.